2002
DOI: 10.1038/sj.tpj.6500123
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic analysis of adverse drug effect reveals genetic variant for susceptibility to liver toxicity

Abstract: A retrospective pharmacogenetic study was conducted to identify possible genetic susceptibility factors in patients in whom the administration of the anti-Parkinson drug, tolcapone (TASMAR), was associated with hepatic toxicity. We studied 135 cases of patients with elevated liver transaminase levels (ELT) of >/=1.5 times above the upper limit of normal, in comparison with matched controls that had also received the drug but had not experienced ELT. DNA samples were genotyped for 30 previously described or new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…Some may have had genetic polymorphisms making them more susceptible to acetaminophen poisoning at lower doses, but most had ingested doses that would be expected to cause severe liver injury. 30,31 A second potential reason for toxicity is the simultaneous use of 2 preparations, recorded in 22% overall, and 38% of the unintentional group. Information was not available regarding the reason for the use of 2 preparations, but frustration, impulsivity, or simply lack of recognition of the presence of acetaminophen in both preparations have all been recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Some may have had genetic polymorphisms making them more susceptible to acetaminophen poisoning at lower doses, but most had ingested doses that would be expected to cause severe liver injury. 30,31 A second potential reason for toxicity is the simultaneous use of 2 preparations, recorded in 22% overall, and 38% of the unintentional group. Information was not available regarding the reason for the use of 2 preparations, but frustration, impulsivity, or simply lack of recognition of the presence of acetaminophen in both preparations have all been recognized.…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that other factors will contribute to the development of tolcapone hepatotoxicity. Indeed, a recent pharmacogenetic study showed that UDP-glucuronosyl transferase, an enzyme involved in the elimination of tolcapone, is associated with tolcapone-induced liver enzyme elevations (44). Thus, genes other than COMT should also be considered for personalized medicine using tolcapone.…”
Section: Orientation Of Catalytic Domain Of Mb-comt Is Critical For Dmentioning
confidence: 99%
“…(6)). For example, a recent retrospective study with 135 patients who had developed increased serum activities of ALT after administration of tolcapone revealed that these patients exhibited a significantly higher increase in single nucleotide polymorphisms (SNPs) in the UGT1A gene complex (UGT is involved in tolcapone elimination) [111]. 6.…”
mentioning
confidence: 99%